1994
DOI: 10.1128/jvi.68.3.2031-2037.1994
|View full text |Cite
|
Sign up to set email alerts
|

Upstream U3 sequences in simian immunodeficiency virus are selectively deleted in vivo in the absence of an intact nef gene

Abstract: Major transcriptional control elements are located within the U3 region of the long terminal repeats (LTRs) of lentivirus and other retroviral genomes. The nef auxiliary gene of simian immunodeficiency virus (SIV) and human immunodeficiency virus overlaps about 70% of the 450to 560-bp-long U3 region present in these primate lentiviruses. We analyzed viral DNA sequences present in rhesus monkeys infected with a mutant of SIVmac containing a 182-bp deletion in the region of nef that does not overlap the LTR. Bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 35 publications
4
36
0
Order By: Relevance
“…4A), suggesting that evolution in this region is driven by pressure to restore Nef function rather than any potential function of this region as part of the 3Ј LTR. This is consistent with recent reports that upstream U3 sequences are deleted in the absence of a functional, intact nef (31) and that extensive mutagenesis of upstream U3 does not significantly alter replicative capacity or virulence in vivo (23), suggesting that the primary function of the overlapping nef/3Ј LTR region is as a nef coding sequence. Sequencing of the SIV-macC8 deletion region from all other animals (except 11R, which was PCR negative by this time) at 33 weeks (29R) or 37 weeks (19R, 28R, 55R, and 57R) postinfection confirmed that the original deletion associated with the parent SIVmacC8 virus had been maintained.…”
Section: Fig 2 Characterization Of Sivmacc8 Behavior In Rhesus Macasupporting
confidence: 92%
See 1 more Smart Citation
“…4A), suggesting that evolution in this region is driven by pressure to restore Nef function rather than any potential function of this region as part of the 3Ј LTR. This is consistent with recent reports that upstream U3 sequences are deleted in the absence of a functional, intact nef (31) and that extensive mutagenesis of upstream U3 does not significantly alter replicative capacity or virulence in vivo (23), suggesting that the primary function of the overlapping nef/3Ј LTR region is as a nef coding sequence. Sequencing of the SIV-macC8 deletion region from all other animals (except 11R, which was PCR negative by this time) at 33 weeks (29R) or 37 weeks (19R, 28R, 55R, and 57R) postinfection confirmed that the original deletion associated with the parent SIVmacC8 virus had been maintained.…”
Section: Fig 2 Characterization Of Sivmacc8 Behavior In Rhesus Macasupporting
confidence: 92%
“…This animal is now being monitored for signs of disease progression and further sequence evolution. It has been reported that additional nef deletions arise in macaques infected with a SIVmac molecular clone containing a 182-bp out-of-frame deletion in nef (SIVmac239⌬nef) constructed so as not to interfere with the overlapping envelope gene and 3Ј LTR (31). Similarly, a defective nef gene isolated from an HIV-1-infected long-term survivor accumulated further substantial nef deletions over time (32).…”
Section: Fig 2 Characterization Of Sivmacc8 Behavior In Rhesus Macamentioning
confidence: 99%
“…For deletions involving vpr and vpx, we have demonstrated the normal expression of adjacent open reading frames (11). While US is probably nothing more than nef coding sequence (13,18,19), it will be treated as a discrete entity for the purpose of this report. Previous publications have described the properties of ⌬nef, ⌬vpr, ⌬vpx, ⌬vpr⌬vpx, and ⌬3 constructs in rhesus monkeys (11,17,35).…”
mentioning
confidence: 86%
“…Two changes in the nef sequence result in nucleotide changes in the overlapping U3 region of the 3Ј LTR (positions 9524 and 9576). Neither of the U3 changes alters the transcriptional control elements identified for SIV; further, the U3 changes that overlap the nef gene have been shown to play no role in virus replication or pathogenesis (6,15,20,45). There is also a nucleotide change in the R region of the 3Ј LTR (position 10063).…”
Section: Construction Of An Infectious Molecular Clone With the In VImentioning
confidence: 99%